Effect of Substance P in Staphylococcus aureus and Staphylococcus epidermidis Virulence: Implication for Skin Homeostasis - N'Diaye, Awa; Mijouin, Lily; Hillion, Mélanie; Diaz, Suraya; Konto-Ghiorghi, Yoan; Percoco, Giuseppe; Chevalier, Sylvie; Lefeuvre, Luc; Harmer, Nicholas J.; Lesouhaitier, Olivier; Feuilloley, Marc G. J. (Frontiers in Microbiology, 2016)
Staphylococcus aureus and Staphylococcus epidermidis are two major skin associated bacteria, and Substance P (SP) is a major skin neuropeptide. Since bacteria are known to sense and response to many human hormones, we investigated the effects of SP on Staphylococci virulence in reconstructed human epidermis model and HaCaT keratinocytes. We show that SP is stimulating the virulence of Staphylococcus aureus and Staphylococcus epidermidis in a reconstructed human epidermis model. qRT-PCR array analysis of 64 genes expressed by keratinocytes in the response to bacterial infection revealed a potential link between the action of SP on Staphylococci and skin physiopathology. qRT-PCR and direct assay of cathelicidin and human β-defensin 2 secretion also provided that demonstration that the action of SP on bacteria is independent of antimicrobial peptide expression by keratinocytes. Considering an effect of SP on S. aureus and S. epidermidis, we observed that SP increases the adhesion potential of both bacteria on keratinocytes. However, SP modulates the virulence of S. aureus and S. epidermidis through different mechanisms. The response of S. aureus is associated with an increase in Staphylococcal Enterotoxin C2 (SEC2) production and a reduction of exolipase processing whereas in S. epidermidis the effect of SP appears mediated by a rise in biofilm formation activity. The Thermo unstable ribosomal Elongation factor Ef-Tu was identified as the SP-interacting protein in S. aureus and S. epidermidis. SP appears as an inter-kingdom communication factor involved in the regulation of bacterial virulence and essential for skin microflora homeostasis.